PERSEPSI DOSEN MENGENAI JAM KULIAH DAN DAMPAKNYA TERHADAP MINAT BELAJAR MAHASISWA - Anita Amelia Ole; Gabriella Alleid Dian Baureh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to present information about lecturers' perceptions regarding class hours, which have an impact on students' interest in learning, information obtained from interviews with several lecturers who teach at one of the private universities in North Sulawesi. The method used is a qualitative descriptive method. The results of this study state that class hours for students have an impact on the interest in learning of each student, for example, if the class is at 07.00 am to 12.00 noon, then the focus to pay attention to the lecturer explaining or fellow students explaining the material in the form of presentations is still very good, so that there is always feedback between lecturers and students or it can be said that the class becomes alive, but if the class starts from 01.00 pm to 06.00 pm, then the students' interest in learning has decreased, there are only a few students who are still active in participating in learning, so a learning method or model is needed that can attract students' interest in learning.